Diversidade, estrutura da rede de interações e fisiologia de epífitas vasculares em áreas urbanas - Palhares, Meirielly Marcelina (2024)
Urbanization, administered as a strong environmental filter, can favor the homogenization of species and the development of plants with specific morphological and physiological characteristics that allow them to overcome obstacles and establish themselves or persist in a community. These plants represent a significant contribution to the species richness and biomass of urban areas, and their variety, abundance and chemical characteristics serve as indicators of environmental disturbances. The study of urban vascular epiphytes is crucial to understand their development and their role as bioindicators of environmental quality. In this dissertation, we raised in Chapter 1 the possibility that the vascular epiphyte community presents low species diversity due to its sensitivity to the impacts of human activity. We predict that beta diversity between the urban area and surrounding native vegetation will be reduced, reflecting the homogenization of urban flora. In Chapter 2, hypotheses were raised that Tillandsia pohliana, T. recurvata and T. loliacea in urban areas present a higher concentration of metallic emissions, due to greater exposure to anthropogenic polluting sources. We expect these elements to accumulate more in the epidermal scales, not penetrating the tissues. Thus, urban Tillandsia would not present significant metabolic changes, maintaining their efficient photochemical performance in the urban environment. In Chapter 1, we highlighted a nesting of urban vascular epiphyte species in relation to the native area, indicating a possible biotic homogenization, probably influenced by the ornamental use of plants and the difficulty in growing these plants. Urban species demonstrated higher generalism, occupying different species of phorophytes and suggesting adaptation to urban conditions. In Chapter 2, we discovered differences in the composition and location of chemical elements in the three Tillandsia species in urban and natural environments. Urban plants had a higher concentration of macronutrients in the epidermal scales compared to the mesophyll. T. recurvata showed greater absorption of atmospheric pollutants, while T. pohliana absorbed less and T. loliacea was more sensitive to urban conditions. We detected few heavy metals, indicating a possible barrier function of the scales. All species maintained photochemical efficiency, with T. recurvata exhibiting greater efficiency, suggesting positive adaptation to pollutants. Tillandsia have proven to be effective for environmental monitoring, detecting variations in air quality in a continuous and accessible way, with the potential to identify critical areas of pollution and guide mitigation and environmental awareness strategies.